2011
DOI: 10.1016/j.yexmp.2011.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to cell surface proteins redirect intracellular trafficking pathways

Abstract: Antibody-mediated intracellular delivery of therapeutic agents has been considered for treatment of a variety of diseases. These approaches involve targeting cell-surface receptor proteins expressed by tumors or viral proteins expressed on infected cells. We examined the intracellular trafficking of a viral cell-surface-expressed protein, rabies G, with or without binding a specific antibody, ARG1. We found that antibody binding shifts the native intracellular trafficking pathway of rabies G in an Fc-independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Additionally, we have previously shown that uptake of antibody-bound membrane proteins can internalize via clathrin through the endosomal pathway (47). In order to further elucidate the mechanisms involved in particle internalization, WT macrophages were stained with fluorescent cholera toxin subunit B (CTxB), which binds to GM1 gangliosides on the cell surface, as a marker for lipid rafts.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we have previously shown that uptake of antibody-bound membrane proteins can internalize via clathrin through the endosomal pathway (47). In order to further elucidate the mechanisms involved in particle internalization, WT macrophages were stained with fluorescent cholera toxin subunit B (CTxB), which binds to GM1 gangliosides on the cell surface, as a marker for lipid rafts.…”
Section: Resultsmentioning
confidence: 99%
“…This might be related to the ability of the intact virus to block degradation in the cell. A recent study indicated that RV-G bound to an antibody transfected in a neuroblastoma cell line is targeted via early and late endosomes to lysosomes (58). In addition, lentiviral vector transduction of dendritic cells involved endosomal trafficking, and its efficiency was enhanced by suppressing autophagy (59).…”
Section: Discussionmentioning
confidence: 99%
“…Ag internalized by these receptors must enter into the late-endosomal/lysosmal Ag pathway for degradation and presentation on MHC class II. It was recently shown that binding of mAbs to the transferrin receptor redirects its native intracellular trafficking (i.e., when bound by its natural ligand, transferrin) from recycling endosomes to late endosomal compartments (61). The extent to which mAb binding affects the internalization pathways of receptors such as BDCA2 and Siglec-H is not known and may be one factor that contributes to the differences in outcomes following targeting Ag to different receptors on pDCs (1).…”
Section: Discussionmentioning
confidence: 99%